Dynamic Evolution Game of Travelers' Air-to-HSR Choice under the Scenario of HSR Speed-Up. (16th January 2021) - Mou, Zhenhua; Yan, Kangli; Li, Kepeng; Shen, Dongfu; Li, Xiang; Wang, Hanbing; Guo, Jijie; Chen, Yanyan
Abstract : With the technological advancement, China's high-speed rail (HSR) has achieved a higher running speed than ever before, which at the same time leads to the intensive competition between air and high-speed rail with trips within 500–1000 km, as well as to the significant changes of travelers' air-to-HSR choice. In order to explore the dynamic adaptation of travelers' choice of high-speed rail (HSR) and air in the case of HSR speed-up, a logit dynamics model of travelers' choice based on evolutionary game was constructed to describe the evolution of travelers' choice. With HSR-air travel time and the ticket price of origin-destination (OD) points of Beijing-Shanghai as the benchmark, the study set up two scenarios of HSR speed-up and compared and analyzed their payoffs in value. On the basis of mathematical simulation, the travelers' "air-to-HSR choice" and the change of competition range under the background of HSR speed-up were both discussed. The result indicated that the HSR speed-up would attract more travelers, and its share rate would rise to 58.31% and 72.73%, respectively, with HSR running speed increasing to 400 and 600 km/h; the marginal utility of HSR speed-up is more obvious, and in the meantime, the increase of HSR running speed extends the intense HSR-air competition range to longer-distance travels. In the case of HSR speed-up, travelers' choice changes as well. The HSR operators themselves should formulate reasonable ticket prices and improve their management. At the same time, the air operators should adjust their operation plan in time.